Molecular detection of a new pathotype enteroaggregative haemorrhagic Escherichia coli (EAHEC) in Indonesia, 2015 - Wahyu Setyarini; Dadik Raharjo; Radita Yuniar Arizandy; Zakaria Pamoengkas; Subijanto Marto Sudarmo; Alpha Fardah Athiyyah; Toshiro Shirakawa (MDPI AG, 2020)
Enteroaggregative haemorrhagic Escherichia coli (E. Coli, EAHEC) has been identified as the agent responsible for one of the largest outbreaks of gastroenteritis and Haemolytic-uremic syndrome (HUS) that is transmitted through food in Germany in 2011. The hypervirulent pathotype has a unique combination of two pathogens namely enterohemorrhagic E.coli strain (EHEC) which produces shiga/verotoxin and enteroaggregative E.coli toxins (EAEC) which produces toxins similar to ST and hemolysin. The toxin produced by the EAHEC strain is a hybrid pathotype that combines the virulence potential of the EAEC and EHEC strains that will damage the microcirculation, cause vasculitis and other toxic effects. The purpose of this study was to determine the percentage of samples infected with enteroaggregative hemorrhagic E. coli bacteria (EAHEC) in pediatric diarrhea patients at DR. Soetomo Hospital, Surabaya, Indonesia, 2015. This study used PCR (Polymerase Chain Reaction) method to detect enteroaggregative E. coli strains (CVD432 and aaic genes) and enterohemorrhagic E.coli (eae gene).The results showed that 33 out of 40 (82,5%) stool samples examined were detected enteroaggregative E. coli (EAEC), 4 out of 40 (10%) enterohemorrhagic E. coli (EHEC) and 3 out of 40 (7,5%) enteroaggregative haemorrhagic E. coli bacteria (EAHEC) , which caused diarrhea in pediatric diarrhea patients at Dr. Soetomo General Hospital. The unique combination of genomic features of the Surabaya outbreak strain, containing characteristics from pathotypes EAEC and EHEC, suggested that it represents a new pathotype enteroaggregative haemorrhagic E. coli (EAHEC). It is expected that development of specific primer design and sequencing are needed to continue in this research.